Impacts of social media on millennials’ investment decisions - Kee, Jia Yin; Lim, Wen Xin; Se, Cheng Jing; Sin, Qian Ying (2025)
This study aims to examine the impacts of social media on investment decisions among Malaysian millennials. Five independent variables are investigated, including influencer credibility, peer influence, fear of missing out (FOMO), financial literacy, and the frequency of using social media, while the dependent variable is millennials’ investment decisions. Data was collected using a structured online questionnaire created with Google Forms and distributed across various social media platforms. The questionnaire was shared with over 1,000 individuals, and after data screening, 403 valid responses out of 445 received were retained for analysis. The data were analysed using SPSS version 31.0. This study employed various analytical techniques, including reliability testing, normality assessment, multicollinearity checks, and multiple linear regression analysis. The results reveal that influencer credibility, peer influence, fear of missing out (FOMO), financial literacy, and the frequency of using social media all play a significant role in shaping millennials’ investment decisions. These findings carry important implications for investors, policymakers, financial regulators, and financial influencers on social media platforms. Additionally, we suggest that future researchers conduct more precise and comprehensive investigations in this field to overcome the limitations identified in our study. Keywords: social media; millennials’ investment decisions; influencer credibility; fear of missing out (FOMO); Theory of Planned Behaviour (TPB) Subject Area: HG179 Personal finance Subject Area: HG4501-6051 Investment, capital formation, speculation Subject Area: HM1176-1281 Social influence. Social pressure